Transthyretin: A Transporter Protein Essential for Proliferation of Myoblast in the Myogenic Program - Lee, Eun Ju (Int J Mol Sci, 2017)
Irregularities in the cellular uptake of thyroid hormones significantly affect muscle development and regeneration. Herein, we report indispensable role of transthyretin (TTR) in maintaining cellular thyroxine level. TTR was found to enhance recruitment of muscle satellite cells to the site of injury, thereby regulating muscle regeneration. Fluorescence-activated cell sorting (FACS) and immunofluorescence analysis of TTR(wt) (TTR wild type) and TTR(kd) (TTR knock-down) cells revealed that TTR controlled cell cycle progression by affecting the expression of Cyclin A2. Deiodinase 2 (D2) mediated increases in triiodothyronine levels were found to regulate the expression of myogenic marker, myogenin (MYOG). Moreover, use of a coumarin derivative (CD) revealed a significant reduction in cellular thyroxine, thereby indicating that TTR play a role in the transport of thyroxine. Taken together, these findings suggest that TTR mediated transport of thyroxine represents a survival mechanism necessary for the myogenic program. The results of this study will be highly useful to the strategic development of novel therapeutics to combat muscular dystrophies.